1996
DOI: 10.4064/fm-150-2-97-112
|View full text |Cite
|
Sign up to set email alerts
|

On homogeneous totally disconnected 1-dimensional spaces

Abstract: On homogeneous totally disconnected 1-dimensional spaces by Kazuhiro K a w a m u r a (Saskatoon), Lex G. O v e r s t e e g e n (Birmingham, Ala.) and E. D. T y m c h a t y n (Saskatoon)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…For the spaces E, E c , and E ω c there is a stronger result: in these spaces σ-compacta are negligible, see [13], [23], and [11].…”
Section: Embedding Into Fans and Complete Erdős Spacementioning
confidence: 99%
See 1 more Smart Citation
“…For the spaces E, E c , and E ω c there is a stronger result: in these spaces σ-compacta are negligible, see [13], [23], and [11].…”
Section: Embedding Into Fans and Complete Erdős Spacementioning
confidence: 99%
“…In [32, §6 Example p.596], Nishiura and Tymchatyn implicitly proved that D e , the set of endpoints of Lelek's fan [27, §9], is not rational at any of its points. Results in [5,6,23] later established D e E c , so E c is nowhere rational. Working in 2 , Banakh [3] recently demonstrated that each bounded open subset of E has an uncountable boundary.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the introduction, E c is a cohesive almost zero-dimensional space. An extrinsic characterization of E c is given by Lelek functions as follows: if [7]. An intrinsic characterization of E c was given in [2].…”
Section: Lemmamentioning
confidence: 99%
“…As mentioned in the previous section, by the extrinsic characterization of E c from [7], in Definition 3.1 we will have that G ϕ↾Xn 0 is homeomorphic to E n for each n ∈ ω. So indeed, E is a countable increasing union of nowhere dense subsets, each homeomorphic to complete Erdős space.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation